Animal traditions : behavioural inheritance in evolution - Avital, Eytan, 1951- (Cambridge University Press, 2000)
Animal Traditions offers an alternative to both the 'selfish gene' and 'meme' views of the world for all evolutionary biologists. By showing how cultural traditions, imparting information from one generation to the next, are vital to birds and mammals, it offers a unified evolutionary and developmental perspective of animal behaviour.